THE CORRELATION BETWEEN PHYSICAL ACTIVITIES AND BALANCE LEVEL IN ELDERLY AT SERENGAN PUBLIC HEALTH CENTER - Aziz, Muhammad Nur; Supriyadi, Arin (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. This study aimed to know the relationship between low physical activity and balance in elderly. Methods. This type of research is a descriptive correlative study between low physical activity and elderly balance that consisting of 37 elderlies in the work area of Serengan Public Health Center based on purposive sampling technique. The examination of low physical activity is through Physical Activity Scale for Elderly (PASE). The questionnaire shows that mean ± SD value of low physical activity is 55.37 ± 18.99 and the balance measurement using Time Up and Go Test (TUGT) that obtained a mean ± SD balance of 18.14 ± 5.67. Results & Analysis. The Spearman-Rank Correlation Coefficient test obtained p value. Discussion. there is a relationship between physical activity and the risk of falling in elderly at Serengan. The lower or less physical activity the elderly does, the higher the risk of falling they have.